Social discounting: Choice between rewards for other people - Jerzy Osiński; Adam Karbowski; Paweł Ostaszewski (Behavioural Processes, 2015)
The purpose of the present study was to test the prediction that when two rewards, a smaller but “socially closer” one and a larger but “socially more distant” one, are moved away from the subject by the same social distance, subjective value of the socially more distant reward will increase (i.e. the rate of social discounting will be shallower). The effect was absent when the recipients were moved back 10 places, but emerged when they were moved back 20 places. In addition, the hyperbolic model was found to correctly describe choices between two socially distant rewards. The results confirm similarities between social and temporal discounting.
Keywords: D01; D03; 330; altruism; social discounting